Editorial: Considering plant metabolites and their synthetic derivatives as candidates for the development of drugs against multidrug resistant (MDR) tumors - Rijo, Patricia (2022)
Despite the great benefits of chemotherapy, the ability of tumor cells to acquire crossresistance to multiple antineoplastic drugs (MDR) results in a drastic reduction in the efficacy of these agents. Of greatest concern is the consequent failure in clinical practice, which remains one of the major barriers to successful cancer treatment. To improve patient outcome, novel efficacious anti-cancer agents or approaches to reverse MDR are necessary. Plants have been an endless and vital source of pharmacologically active compounds, many of which are widely used in cancer therapies, not only to control tumor cells, but also to increase their sensitivity to chemotherapeutic agents. The structural diversity and array of biological properties of plant-derived metabolites, in particular against tumors, make these strong candidates to combat MDR cells or establish their scaffolds as a valuable base for the synthesis of derivatives. This enormous potential of plants to tackle MDR tumors encouraged us to publish this Research Topic to display and discuss the cutting-edge research in the field. As editors, it was a pleasure to review a wide range of fascinating articles with different perspectives, and we summarize here the main findings of accepted articles.